INTEGRATION OF CSR PROJECTS IN COAL MINING ACTIVITIES IN ACEH - Muhammad Dhafi Iskandar (Prosiding Temu Profesi Tahunan PERHAPI, 2020)
Indonesia with its vast number of coal resources and natural resources exploitation and mining operational activities are expected to bring economic impacts both in terms of infrastructure, Corporate Social Responsibility (CSR), employment, etc., which is in line with the concept of business ethics and the essence of rights and duties in society. Yet, many problems that are supposed to be solved with such potentials are not effectively reduced or diminished. Government regulation states that companies are required to develop community development and empowerment programs in the vicinity of the mining area which must first be consulted with the local government and communities, where they can propose a program. Those are prioritized to the surrounding communities that are directly affected by mining activities, regardless of administrative boundaries of the district area. This research was conducted through observation, interviews, reports, and papers from coal mining companies and related institutions on action planning research methods which then focused on analysing the development of mining in Aceh, where the hypothesis that emerged is regarding the possibility to combine mining, forestry products, plantation, poultry, and fishery in the coal mining concession area in Aceh to reduce the negative impact. Collaboration with the local community can be utilized for village development and construction of mining company’s needs, along with the potential to produce additional profits for both parties. Hence, this could serve as a solution to illegal logging and mining as well as land burning and conflicts, through the system of cooperation and profit sharing. Additional programs on health, education and infrastructure that are based on surveys and research produce appropriate results according to the root of the problem and actual needs, which the community may not have previously realized.